2014
DOI: 10.3727/096504013x13854886566598
|View full text |Cite
|
Sign up to set email alerts
|

The Sirtuin Inhibitor Tenovin-6 Upregulates Death Receptor 5 and Enhances Cytotoxic Effects of 5-Fluorouracil and Oxaliplatin in Colon Cancer Cells

Abstract: It has been reported that upregulated SIRT1 (NAD+-dependent class III histone deacetylase) deacetylates the p53 protein, represses its function, and allows for tumor cell growth in various cancers. Here we investigated antitumor effects of tenovin-6, a small-molecule inhibitor of SIRT1 and SIRT2, in various colon cancer cell lines. Tenovin-6 induced apoptosis in all five colon cancer cell lines investigated (two cell lines with wild-type p53 and three with mutant p53) regardless of the p53 mutation status. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Tenovin-6 has since been used as an inhibitor of SIRT1 in a number of studies. 1, 3, 4, 5, 6, 9, 10, 11, 12, 13, 14, 15, 16 As SIRT1 regulates the autophagic pathway, 29, 30, 31 we examined whether knockdown of SIRT1 was sufficient to mimic the effect of tenovin-6 on LC3B-II accumulation. SIRT1 knockdown did not cause LC3B-II accumulation in A549, Huh7 and OCI-Ly1 cells; in contrast, it slightly reduced the LC3B-II levels (Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tenovin-6 has since been used as an inhibitor of SIRT1 in a number of studies. 1, 3, 4, 5, 6, 9, 10, 11, 12, 13, 14, 15, 16 As SIRT1 regulates the autophagic pathway, 29, 30, 31 we examined whether knockdown of SIRT1 was sufficient to mimic the effect of tenovin-6 on LC3B-II accumulation. SIRT1 knockdown did not cause LC3B-II accumulation in A549, Huh7 and OCI-Ly1 cells; in contrast, it slightly reduced the LC3B-II levels (Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
“…Tenovin-6 has attracted significant interest because it was originally identified as a potent p53 activator, and shown to have direct inhibitory effect on the protein deacetylase activity of purified human SIRT1, SIRT2 and SIRT3 in vitro with IC50 values of 21, 10 and 67  μ M, respectively. 1, 2 Since then, tenovin-6 has been widely used as an inhibitor of sirtuins, especially SIRT1, and demonstrated to have a promising anti-neoplastic effect in vitro or in vivo on hematopoietic malignancies including chronic myelogenous leukemia, 3, 4, 5, 6 chronic lymphocytic leukemia (CLL), 7, 8 acute lymphoblastic leukemia, 9 acute promyelocytic leukemia 10 and solid tumors such as pancreatic cancer, 11 colon cancer, 12 gastric cancer, 13 Ewing sarcoma, 14 soft tissue sarcoma 15 and uveal melanoma. 16 Tenovin-6 was used at doses (1–10  μ M) much lower than the IC50 values for sirtuins in most of these studies; however, it still strongly induced cell arrest or apoptosis, suggesting that it may have a function other than inhibiting sirtuins.…”
mentioning
confidence: 99%
“…Moreover, the gene product of GALNT14 is an enzyme that catalyzes O -glycosylation of many proteins including the DR-4 and -5. It has been reported that the cytotoxic effects of oxaliplatin in CRC can be enhanced by tenovin-6 through upregulating DR-5, 14 suggesting that modulation of DR-mediated signaling may affect the effects of oxaliplatin-based chemotherapy. In this study, 1 convenient explanation for the GALNT14 genotypes–associated therapeutic outcomes is the differential intensities of DR-mediated apoptosis signaling between the “TT” and “non-TT” genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In CRC cells, it has been demonstrated that the increase of DR-5 enhances cytotoxic effects of 5-fluorouracil and oxaliplatin. 14 Here, we hypothesized that the GALNT14 genotype might also affect the outcome of stage III CRC patients and examined the clinicopathological parameters in relationship to GALNT14 genotype and the prognosis predictive values of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies previously reported the anticancer effects of SIRT1 inhibitors. Ueno et al 40 showed that tenovin-6, an inhibitor of SIRT1 and 2, induced apoptosis in five colon carcinoma cell lines regardless of the p53 mutation status, and the synergistic antitumor effects of tenovin-6 were also observed in combination with either 5-FU or oxaliplatin. In contrast, Kabra et al 41 reported that EX527 (2 μM), which is highly specific to SIRT1, but not SIRT2, enhanced the proliferation of the colon cancer cell line, HCT116.…”
Section: Discussionmentioning
confidence: 99%